Potential of ethanol to reduce grapevine transpiration - Neila Ait Kaci; Beatrice Quinquiry; Alice Diot; Olivier Yobregat; Anne Pellegrino; Pierre Maury; Christian Chervin (OENO One)
This study investigates whether ethanol (EtOH) modulates response to drought in grapevine, as demonstrated previously in Arabidopsis, rice and wheat. We ran a potted-cutting experiment with a progressive soil water deficit. Plants pre-treated with 250 mM EtOH solutions exhibited slower depletion of the fraction of transpirable soil water (FTSW), compared to controls. While 250 mM EtOH decreased transpiration in the early days, these EtOH pre-treated plants maintained higher leaf transpiration than controls after 10 days of soil water depletion. The FTSW threshold for the transpiration process was significantly higher in plants treated with 250 mM EtOH than in controls. These results suggest that EtOH may alter grapevine response to drought, leading to potential water savings in wine-growing regions prone to high water shortages, linked to climate change. This should encourage further testing under various vineyard conditions.